FUZZY SET ASSESSMENT OF INNOVATIVE PROJECT EFFECTIVENESS PARAMETERS - A. O. Baranov; E. I. Musyko; V. N. Pavlov (Финансы: теория и практика)
Investments made by venture capital funds are characterized by high uncertainty and risk, and quite often they have a step-by-step implementation scenario. In this regard, the traditional discounted cash flow method can be supplemented with other approaches that take into account the flexibility in decision-making, in particular, by assessing the effectiveness of an innovative project with methods that are used abroad but so far have not found wide application in Russia. One of these methods is the method of real options. The traditional analysis of the innovation project effectiveness can also be augmented by the study of the impact of the uncertainty of future cash flows generated by the project on the effectiveness indices using the method of fuzzy sets. The application of real options as well as fuzzy sets is, according to the authors, a way to improve the existing methods of assessing the cost-effectiveness of innovative projects. The paper is devoted to fuzzy-set assessment of the sustainability of financial flows generated by an innovative project and its effectiveness indices. Briefly described is a methodology for estimating the reliability and stability of the fuzzy metrics. The results of computing fuzzy set indices to assess the cost effectiveness of real innovative projects implemented in the territory of Russia and funded by venture capital funds are provided. A meaningful interpretation of the results obtained is given. The use of the fuzzy-set approach to the value assessment of a composite call option by the Geske-Hsu model giving additional opportunities is described.